2004
DOI: 10.1108/14676370410512599
|View full text |Cite
|
Sign up to set email alerts
|

An environmental management qualification through distance education

Abstract: The department of geography and environmental studies of the University of South Africa recently played a pivotal role in implementing an inter-and multidisciplinary undergraduate programme in environmental management. This programme prepares students for entry-level occupations, and equips them with the knowledge, skills and values needed to contribute to sustainable development. Both BA and BSc students are catered for, which contributes to the broadening of undergraduate education. This programme is unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Pretorius [7] cites various references placing distance education in the context of a teaching and learning process in which the educator and learner are removed from each other in time and space and which typically involves a combination of different media. He points out that this form of education is no longer viewed as a 'second class' option.…”
Section: Translating Training Needs Into Action By Distance Learningmentioning
confidence: 99%
“…Pretorius [7] cites various references placing distance education in the context of a teaching and learning process in which the educator and learner are removed from each other in time and space and which typically involves a combination of different media. He points out that this form of education is no longer viewed as a 'second class' option.…”
Section: Translating Training Needs Into Action By Distance Learningmentioning
confidence: 99%
“…This observation is based on financial viability, trends in student numbers, and relevance for society. Pretorius (2004) and Zietsman and Pretorius (2006) observed that student numbers for the programme were gradually increasing, with students from all over South Africa and farther afield. Although it can be anticipated that this growth will level off, a baseline in terms of the minimum number of students required to continue to offer this qualification, has been established.…”
Section: Successes Versus Challengesmentioning
confidence: 99%
“…Although it can be anticipated that this growth will level off, a baseline in terms of the minimum number of students required to continue to offer this qualification, has been established. Earlier in 2000, Pretorius (2004) found that a large majority of students in the EM programme were already employed in the environmental industry, and that the programme provided a means to receive formal education in environmental management. This indicated that the programme was an option for people already employed in the environmental industry, and lacking the required theoretical background.…”
Section: Successes Versus Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of formation exists even within business school teaching staff and consequently management is not adequately prepared to account for the environment as a key issue in decisionmaking processes (Barratt, 2006;Pretorius, 2004;Dominik et al, 2003;Bunch and Finlay, 1999). This is particularly problematic for small-and medium-sized enterprises (SMEs).…”
Section: Introductionmentioning
confidence: 98%